Malaysian agricultural development toward the 2000s - an information technology perspective - Han, Chun Kwong; Gibbons, Eric T.; Mohaiyidin, Mohd. Ghazali (1985)
As the information society evolves into a socio-economic reality in South East Asia, the agriculture sector will be undergoing a fundamental transformation along with the other segments of the economy. With the shift from capital and natural resources to information as the strategic resourse, agriculture's share of the nation's wealth will diminish disproportionately unless due initiatives are taken to ensure the centrality of information technology in agriculture development. In this paper, a scenario is generated of an agricultural sector energised by knowledge information processing systems. The full potential of information technology are examined. It is concluded that information technology should be considered as a critical success factor in maximising agricultural productivity and profitability as the world enters the Information Age.